The Ignatian Art of Spiritual Conversation - Austin, Nicholas ca. 21. Jh. (2023)
The article explores the concept of "spiritual conversation" in the Ignatian tradition, emphasizing its importance and transformative power in relationships with others and with God. It delves into Ignatius Loyola's passion for spiritual conversation and its significance in the development of the Society of Jesus, highlighting its relevance in various aspects of contemporary spiritual ministry and discernment.
Keywords: Discernment of spirits; God; Ignatius, of Loyola, Saint, 1491-1556; Jesuits; Spirituality